Blocking of EphA2 on Endometrial Tumor Cells Reduces Susceptibility to Vδ1 Gamma-Delta T-Cell-Mediated Killing - Hudecek, Robert; Kohlova, Barbora; Siskova, Ingrid; Piskacek, Martin; Knight, Andrea (Frontiers in Immunology, 2021)
Background: Endometriosis is a common gynecological disease characterized by the presence of endometrial tissue outside the uterus causing chronic inflammation, severe pain and infertility. However, the innate immunity of gamma-delta (γδ) T lymphocytes in endometriosis has not been characterized. The tyrosine kinase EphA2 is often overexpressed in cancer. Methods: We analyzed Vδ1 and Vδ2 γδ T cells in peripheral blood and paired peritoneal fluid samples in endometriosis patients (n=19) and compared the counts to that of age and sex matched healthy donors (n=33) using flow cytometry. Vδ1 and Vδ2 T cells from healthy donors were used against KLE, RL-95 and Ishikawa endometrial tumor cells in 4h flow cytometric cytotoxicity assays. The EphA2 blocking studies were performed using antibody, small-molecule inhibitor ALW-II-41-27 and the CRISPR/Cas9. Results: We determined Vδ1 T cells substantially reduced in patients’ peripheral blood (p<0.01) and peritoneal fluid (p<0.001). No differences were found for circulating Vδ2 T cells compared to peritoneal fluid throughout the menstrual cycle. We observed prominent cytotoxic reactivity of γδ T lymphocytes against endometrial tumors. Importantly, we found reduced specific lysis of EphA2-positive cell lines KLE and RL-95 by Vδ1 T cells in the EphA2 antibody blocking studies. Furthermore, Vδ1 T cell-mediated killing was significantly decreased in RL-95 cells EPHA2 knockout. Finally, potent cytolytic activity exerted by Vδ1 T cells was abolished by using the EphA2 inhibitor. Conclusions: We determined variable levels of Vδ1 and Vδ2 γδ T cells in endometriosis patients. We observed inherent cytotoxic reactivity of γδ T cell subsets against endometrial cell lines. Specifically, we found that blocking of EphA2 expression resulted in significant inhibition of endometrial tumor killing mediated by Vδ1 γδ T cells. These results suggest that EphA2 is involved in tumor cell lysis and contributes to susceptibility to Vδ1 γδ T cells cytotoxic reactivity.